A combined upflow anaerobic sludge bed and trickling biofilter process for the treatment of swine wastewater. Issue 10 (18th May 2016) - Zhao, Bowei; Li, Jiangzheng; Buelna, Gerardo; Dubé, Rino; Le Bihan, Yann
ABSTRACT: A combined upflow anaerobic sludge blanket (UASB)-trickling biofilter (TBF) process was constructed to treat swine wastewater, a typical high-strength organic wastewater with low carbon/nitrogen ratio and ammonia toxicity. The results showed that the UASB-TBF system can remarkably enhance the removal of pollutants in the swine wastewater. At an organic loading rate of 2.29 kg/m 3 d and hydraulic retention time of 48 h in the UASB, the chemical oxygen demand (COD), Suspended Solids and Total Kjeldahl Nitrogen removals of the combined process reached 83.6%, 84.1% and 41.2%, respectively. In the combined system the UASB served as a pretreatment process for COD removal while nitrification and denitrification occurred only in the TBF process. The TBF performed reasonably well at a surface hydraulic load as high as 0.12 m 3 /m 2 d. Since the ratio of influent COD to total mineral nitrogen was less than 3.23, it is reasonable to suggest that the wood chips in TBF can serve as a new carbon source for denitrification.